Treatment of adult metachromatic leukodystrophy model mice using intrathecal administration of type 9 AAV vector encoding arylsulfatase A - Noriko Miyake; Koichi Miyake; Atsushi Sakai; Motoko Yamamoto; Hidenori Suzuki; Takashi Shimada (Scientific Reports, 2021)
Abstract Metachromatic leukodystrophy (MLD) is a lysosomal storage disease caused by an arylsulfatase A (ARSA) deficiency and characterized by severe neurological symptoms resulting from demyelination within the central and peripheral nervous systems. We investigated the feasibility and efficacy of intrathecal administration of a type 9 adeno-associated viral vector encoding ARSA (AAV9/ARSA) for the treatment of 6-week-old MLD model mice, which are presymptomatic, and 1-year-old mice, which exhibit neurological abnormalities. Immunohistochemical analysis following AAV9/ARSA administration showed ARSA expression within the brain, with highest activities in the cerebellum and olfactory bulbs. In mice treated at 1 year, alcian blue staining and quantitative analysis revealed significant decreases in stored sulfatide. Behaviorally, mice treated at 1 year showed no improvement in their ability to traverse narrow balance beams as compared to untreated mice. By contrast, MLD mice treated at 6 weeks showed significant decreases in stored sulfatide throughout the entire brain and improved ability to traverse narrow balance beams. These findings suggest intrathecal administration of an AAV9/ARSA vector is a promising approach to treating genetic diseases of the central nervous system, including MLD, though it may be essential to begin therapy before the onset of neurological symptoms.